2020
DOI: 10.1002/jpen.1811
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Support Teams: A Systematic Review

Abstract: BackgroundThe concept of a nutrition support team (NST) was first introduced at the end of the 20th century in the US and Europe. Expected benefits include reduced (inappropriate) prescription of (par)enteral nutrition; however, to the authors’ knowledge, no recent review has assessed the effectiveness of NSTs. Therefore, this systematic review evaluated the effectiveness of NSTs with respect to the prevalence of adult patients receiving (par)enteral nutrition.MethodsFive literature databases were searched and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 78 publications
1
29
0
7
Order By: Relevance
“…A systematic review by Mistiaen et al (2020), stated, that there is weak evidence that Nutrition Support Teams increase appropriate EN use in ICU patients. A decrease of the duration of PN could not be shown [34].…”
Section: Verificationmentioning
confidence: 81%
“…A systematic review by Mistiaen et al (2020), stated, that there is weak evidence that Nutrition Support Teams increase appropriate EN use in ICU patients. A decrease of the duration of PN could not be shown [34].…”
Section: Verificationmentioning
confidence: 81%
“…Previous systematic reviews primarily evaluated PN appropriateness and the enteral nutrition (EN) to PN trend 17,18 . These literature reviews found a decrease in inappropriate PN use and an increase in the EN to PN use ratio after NST introduction 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews primarily evaluated PN appropriateness and the enteral nutrition (EN) to PN trend 17,18 . These literature reviews found a decrease in inappropriate PN use and an increase in the EN to PN use ratio after NST introduction 17,18 . Both reviews restricted eligible studies to those published after 2000 and neither performed meta‐analyses nor graded the evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Erschwerend kommen Schwankungen der Arbeitsbelastung in allen Aufgabenbereichen hinzu. Die unklare Zuordnung der Arbeitszeit zur Tätigkeit im Ernährungsteam zeigt sich auch in der Übersichtsarbeit von Mistiaen et al (2020), die Publikationen zu Ernährungsteams aus 11 Ländern auswerteten [10]. Damit hat sich die Situation, wie sie von Senkal bereits 2002 beschrieben wurde, offensichtlich nicht verbessert [15].…”
Section: Diskussionunclassified